Family Support Connection To Wards Mother Behavior In Give Asi Exclusive At Puskesmas Gayaman Mojokerto - Siti Nur Farida; Wahyu Anjas Sari (Universitas STRADA Indonesia, 2020)
ASI exclusive gift ASI (mother milk water) beginning may be after give birth, given without time-table and is not given food other, although only plain water, until aged baby 6 months. To avoid the happening of family support less in give ASI exclusive need information about the important ASI for baby and family support enhanced (instrumental, informational, evaluation, emotional). Watchfulness aim analyze family support towards mother behaviour in gift ASI exclusive at Puskesmas Gayaman Mojokerto Researcher design that used cross sectional. Research date 1 Mei- 30 Julies 2010. Population in this research entire mothers that gives suck age 0-6 month at Puskesmas Gayaman Mojokerto as much as 52 respondents. Big sample numbers 46 respondents, family support independent variable and variable dependent mother behaviour. The instrument uses questionnaire and sample taking technical purposive sampling. Then tested by using correlation test spearman rank (rho) at obtain? = 0,024 <? = 0,05. From this research result shows that get family support deliver it less support (9%), enough support (48%), support (43%). While respondent based on mother behaviour in give ASI exclusive deliver it (65%) good mother behaviour, (22%) unfavourable mother behaviour, (13%) mother behaviour not good. Based on analysis result uses correlation test spearman rank (rho) at obtain ρ = 0,024 <α = 0,05 mean found connection between family support with mother behaviour in give ASI exclusive at Puskesmas Gayaman Mojokerto. Based on this research result inferential that there is family support connection towards mother behaviour in give ASI exclusive at Puskesmas Gayaman Mojokerto